Community-Based Total Sanitation (CLTS) As A Strategy To Enhance Environmental Health In Disaster-Prone Villages: A Case Study In Pujiharjo, Malang, Indonesia - Meyralda Dara Adisa; Pujo Widodo; Anwar Kurniadi; Wilopo (International journal of technology and education research, 2026)
Pujiharjo Village in Malang Regency is a coastal area frequently affected by floods, posing significant environmental health challenges. This study aims to analyze the implementation of Community-Based Total Sanitation (CLTS) as a strategy to strengthen environmental health and disaster preparedness in disaster-prone communities. A descriptive case study design was applied using secondary data from the 2024 CLTS monitoring survey in Pujiharjo. A total of 1,369 households were analyzed based on five CLTS pillars. Data collection involved structured household surveys and laboratory water quality testing. Descriptive statistics were used to evaluate the percentage of households meeting CLTS indicators and to identify gaps compared with national and international standards. The study found high achievements in hygiene-related pillars, namely handwashing with soap (86.41%) and food and water management (95.76%), indicating improved household health behavior. However, the low performance in solid (41.12%) and liquid (29.88%) waste management highlights weaknesses in sanitation infrastructure and community participation. These conditions increase environmental contamination risks, especially during floods. Integrating CLTS into disaster preparedness programs is essential to enhance resilience and reduce vulnerability to environmental health hazards. Strengthening community participation, sanitation infrastructure, and intersectoral coordination is crucial to improve environmental health resilience in disaster-prone areas like Pujiharjo Village